Assessment of the Optimal Operating Parameters during Extracorporeal CO2 Removal with the Abylcap® System. Issue 11 (November 2016) - Eloot, Sunny; Peperstraete, Harlinde; De Somer, Filip; Hoste, Eric
Purpose: Lung protective ventilation is recommended in patients with acute respiratory distress syndrome (ARDS) needing mechanical ventilation. This can however be associated with hypercapnia and respiratory acidosis, such that extracorporeal CO2 removal (ECCO2 R) can be applied. The aim of this study was to derive optimal operating parameters for the ECCO2 R Abylcap® system (Bellco, Italy). Methods: We included 4 ARDS patients with a partial arterial oxygen tension over the fraction of inspired oxygen (PaO2 /FiO2 ) lower than 150 mmHg, receiving lung-protective ventilation and treated with the Abylcap® via a double lumen 13.5-Fr dialysis catheter in the femoral vein. Every 24 hours during 5 consecutive days, blood was sampled at the Abylcap® inlet and outlet for different blood flows (QB :200-300-400 mL/min) with 100% O2 gas flow (QG ) of 7 L/min, and for different QG (QG : 0.5-1-1.5-3-6-8 L/min) with QB 400 mL/min. CO2 and O2 transfer remained constant over 5 days for a fixed QB . Results: We found that, for a fixed QG of 7 L/min, CO2 transfer linearly and significantly increased with QB (i.e. from 58 ± 8 to 98 ± 16 mL/min for QB 200 to 400 mL/min). For a fixed QB of 400 mL/min, CO2 transfer non-linearly increased with QG (i.e. from 39 ± 9 to 98 ± 16 mL/min for QG 0.5 to 8 L/min) reaching a plateau at QG of 6 L/min. Conclusions: Hence, when using the Abylcap® ECCO2 R in the treatment of ARDS patients the O2 flow should be at least 6 L/min while QB should be set at its maximum.